Hubungan Antara Kondisi Lingkungan Sekolah Dengan Aktivitas Belajar Siswa SMA Shailendra Palembang - Asmareni, Juwita; Ramadhani, Erfan; Nurlela, Nurlela (Indonesian Research Journal on Education, 2023)
The learning process is carried out by explaining and student activities are only limited to listening, taking notes and answering when asked questions by the teacher. This teaching andlearning process clearly does not encourage students to be active and creative. The purpose of this study was to determine the relationship between the condition of the school environment and the learning activities of high school students Shailendra Palembang. The research method used in this study is the correlational method. The variables of this study consisted of the independent variable, namely the condition of the school environment and the dependent variable, namely learning activities. The population in this study were all students of class X at SMA Shailendra Palembang, while the sampling technique was based on a total sampling of 47 students. The data collection technique used a questionnaire technique, while the data analysis technique used the product moment formula. The results showed that the average condition of the school environment was 126.19 and the average learning activity was 127.77. This means that the average learning activity is higher than the school environment. Based on the results of the study, the condition of the school environment has a significant relationship with student learning activities at SMA Shailendra Palembang, as evidenced by the results of hypothesis testing with a value of rcount = 0.543 > rtable = 0.288.